The Effect of Using Song on Students’ Achivement in Simple Past Tense at SMK Antartika 2 Sidoarjo - Yuanita Eka Puspita (Proceedings of The ICECRS, 2021)
SongIn English making sentence in the correct language order is difficult for students because English is a forein language. In this research focus on simple past tense. This research was coducted on tenth grade students in SMK Antartika 2 Sidoarjo who have understanding problems in simple past tense. This research aims to determine wether there is a significant influence on students achievement in simple past tense. This study used the pre-experimental design with Wilcoxon Sign Rank test and saturated sample technique. The researcher use the song as media in delivery of simple past tense to make it easier to understand.